Analysis and Mitigation of Strategic Risk Business Process by Considering Relationship between Risks: Case Study in Electricity Generation Companies - Lalu Bramantias Gutama,; I Nyoman Pujawan, (Jurnal Sosial Humaniora, 2025)
This study analyzes the linkages between the causes of strategic risks of business processes which refer to the balance scorecard perspective in company X, one ofelectricity generation company. Prioritized 87 risk causes were identified at the outset using the House of Risk 1 method and the Pareto principle so that 17 dominant risk causes were obtained, which were then analyzed using the ISM method and then weighted using the analytic network process (ANP) method to obtain the new ARP value causes risk that had accommodated the relationship between the causes of risk. To make it easier for companies to prioritize the handling of the 17 risk-causing agents, a mitigation analysis was then carried out using the House of Risk 2 by considering the ranking of existing effectiveness to difficulty so that 8 effective strategies for handling agents causing risk were chosen.